2023
DOI: 10.3389/fmicb.2022.1085214
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic turnover of cysteine-related thiol compounds at environmentally relevant concentrations by Geobacter sulfurreducens

Abstract: Low-molecular-mass (LMM) thiol compounds are known to be important for many biological processes in various organisms but LMM thiols are understudied in anaerobic bacteria. In this work, we examined the production and turnover of nanomolar concentrations of LMM thiols with a chemical structure related to cysteine by the model iron-reducing bacterium Geobacter sulfurreducens. Our results show that G. sulfurreducens tightly controls the production, excretion and intracellular concentration of thiols depending on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…We recently demonstrated that G. sulfurreducens methylate cysteine to penicillamine in response to the addition of exogenous cysteine. 42 This process has potentially substantial implications on MeHg production since it has been demonstrated that Hg(II) methylation by G. sulf urreducens is consistently enhanced by cysteine, but not by penicillamine. 16,22 The response in Hg(II) methylation following the addition of 100 or 600 nM exogenous cysteine differed among the three assays.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently demonstrated that G. sulfurreducens methylate cysteine to penicillamine in response to the addition of exogenous cysteine. 42 This process has potentially substantial implications on MeHg production since it has been demonstrated that Hg(II) methylation by G. sulf urreducens is consistently enhanced by cysteine, but not by penicillamine. 16,22 The response in Hg(II) methylation following the addition of 100 or 600 nM exogenous cysteine differed among the three assays.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A sample was collected by filtration (0.2 μm pore size PES syringe filters) at the late exponential growth phase. This filtrate was added to the assay buffer (10% v/v) to comprise the metabolite medium, which contained biogenic metabolites including enhanced concentrations of cysteine and other LMM-thiols …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations